Identity assimilation: Impact of conflict and partition on the giving behaviors of refugees and natives in West Bengal - Nilanjan Bhattacharya; Debayan Pakrashi; Sarani Saha; Liang C. Wang (Global Labor Organization (GLO), 2023)
In regions affected by conflicts, partition, and violence, how does past exposure to such incidences affect attitudes towards members of different social groups? Drawing on the theory of inequity aversion model, we infer that past exposure to conflict and violence can increase an individual's ability to empathize with the ingroup(s) and discriminate against the outgroup(s). We test this hypothesis by conducting a money-giving dictator game and a money-taking dictator game among 794 Hindu Bengali individuals from an Indian-native-born background and an East-Pakistan-refugee background residing in the state of West Bengal in India. Our objective is to study the dominant social identity and identity assimilation of individuals with multiple social affiliations. We find that participants from both native and refugee backgrounds show favoritism towards other Hindus in India by giving them money taken away from Muslims in India, Hindus in Bangladesh, and Muslims in Bangladesh. The favoritism towards other Hindus in India indicates that they are treated as the social ingroup, while the discrimination against the other groups indicates that they are treated as the social outgroups. Participants from refugee families discriminate against Muslims in India more than Hindus in Bangladesh, while participants from native families discriminate against Hindus in Bangladesh more than Muslims in India. The differential treatments across social groups suggest that the Hindu religious affiliation plays a more dominant role than the Indian nationality affiliation in the identity of refugees. Further, we find suggestive evidence of identity assimilation among individuals with a refugee background.
Keywords: F22; J15; Z12; N3; 330; social identity; partition refugees; charitable giving